2015
DOI: 10.15282/jmes.9.2015.10.0158
|View full text |Cite
|
Sign up to set email alerts
|

A simplified design of clamping system and fixtures for friction stir welding of aluminium alloys

Abstract: Sound friction stir welds could be attained by using an active design of backing/clamping system with a proper selection of the welding parameters. This work presented a simplified design of fixtures and backing plates to be used for friction stir welding of aluminum alloys. The test-rig was constructed to prevent dispersal or lifting of the specimens throughout the joining process and to ensure uniform distribution of temperature along the plates. The workpieces were subjected to uniform lateral and vertical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Using the specially constructed fixture as shown in Figure 2 to clamp the welding plates, the welding studies were carried out on an automated vertical milling machine. The most important element in FSW to prevent the lifting of the plates to be welded during the welding phase and to verify coherent temperature distribution across the sample plates is the appropriate fixture design with backing plates [18]. The welding variables were adapted to generate defect-free welds based on visual inspection.…”
Section: Methodsmentioning
confidence: 99%
“…Using the specially constructed fixture as shown in Figure 2 to clamp the welding plates, the welding studies were carried out on an automated vertical milling machine. The most important element in FSW to prevent the lifting of the plates to be welded during the welding phase and to verify coherent temperature distribution across the sample plates is the appropriate fixture design with backing plates [18]. The welding variables were adapted to generate defect-free welds based on visual inspection.…”
Section: Methodsmentioning
confidence: 99%
“…Each zone experiences dissimilar plastic deformations, leading to different shapes of microstructure. In order to produce a sound welding joint, welding parameters such as rotational speed, transverse speed, and position of the metals either on the advancing or retreating side should be considered during the FSW process [13][14][15]. Research by Dawood et al [16] found that reduction in surface roughness reduces friction and narrows down the HAZ at the welding joint.…”
Section: Introductionmentioning
confidence: 99%
“…Arc welding is a type of welding that uses a welding power supply to create an electric arc between an electrode and the base material to melt the metals at the welding point. Gas tungsten arc welding is also called as TIG welding [6][7][8][9]. Tungsten inert gas (TIG) welding is an arc welding process that produces coalescence of metals by heating them with an arc between a non-consumable electrode and the base metal.…”
Section: Introductionmentioning
confidence: 99%